Phases with layered (AB) and “defective” (A2B3) structures in AIII–BVI systems. Part 2. Phase diagrams and approaches to some problems of reproducible synthesis in AIII– BVI systems. Review - Alexander Y. Zavrazhnov; Nikolay Y. Brezhnev; Ivan N. Nekrylov; Andrew V. Kosyakov (Конденсированные среды и межфазные границы)
The paper analyzes phase diagrams of AIII–BVI systems and phase equilibria involving crystalline compounds formed in these systems. The location of each solid binary phase mainly related to mono- and sesquisulfides families and selenides of aluminum, gallium, and indium on T-x-diagrams is discussed in detail. The homogeneity regions of these phases were also analyzed if the necessary data were available. For polymorphic (or close to them) transformations, the nature of the occurring structural transformations was described and the temperature stability of various modifications of similar composition was analyzed. Using examples of several systems, it was shown how, by changing the experimental conditions, it is possible to reproducibly obtain compounds with the required structure (even for different polytypes of structures with very similar structures of individual layers) and the required composition (including those within the regions of phase homogeneity). Various methods of reproducible inorganic synthesis were considered, taking into account the features of the phase diagram and phase equilibria. In conclusion, current and partially still unresolved issues concerning the characteristics of the A2IIIB3VI and A1IIIB1VI compounds were analyzed